Diseño de un plan financiero y una estrategia de control, utilizando como herramienta el flujo de caja para el comisariato “QR” año 2012 - Noboa Tobar, Erika Gabriela (2013)
Now Companies has increased the need for good financial control system that allows them to measure the efficiency and productivity of your business. It should be noted that companies that apply internal controls will always be aware of the real situation being experienced, here comes the importance of financial planning not only to verify the compliance of an effective financial control but also can have a clear vision about the results to be achieved in the future allowing anticipate and make decisions on behalf of their progress and growth. This research aims at essential design a financial plan and a control strategy for the Commissariat "QR" Canton Valencia, in order to provide a tool Administrative Management - Financial that allows timely decisions regarding the profitability currently owns the business. For the development of research methodological procedures were used that facilitated significant research and obtaining further understanding of financial information. The Commissariat "QR" is characterized as a medium-sized business and in which their owners since they began their activities have never used any kind of financial planning and even less financial control activities for your business.